Development of Ready-To-Eat ‘Banana Flower Keropok Lekor’ by using Retort Processing Technology (Banana Blossom) - Soulihen, Noormaisarah; Kormin, Faridah (Enhanced Knowledge in Sciences and Technology, 2025)
The development and evaluation of a novel plant-based alternative to traditional Malaysian keropok lekor presents an innovative approach to meet evolving consumer preferences in the ready-to-eat (RTE) food sector. This investigation focuses on the four formulations of keropok lekor incorporating banana flower in combination with shredded coconut, oyster mushroom, and potato as key ingredients. Physicochemical assessments focus on critical quality indicators such as moisture content, colour metrics, pH levels, and texture profile analysis (TPA). Formulation 3 exhibited moisture levels (56.02%) which is the most comparable to traditional products while other formulation in the range of 50%-60%. From the result, the pH is range from 6.00 until 6.94 and hardness measurements exhibited a broad range from 1612.71 to 5295.18. Sensory parameters under examination include appearance, aroma, colour, texture, and taste characteristics for 50 untrained panellists. The nutritional value indicated this product as a suitable alternative for calorie-conscious consumers due to the total fat content was determined to be 2.8g/100g, the energy content analysis revealed 189 kcal/100g and the sodium content is 412.8mg/100g. This research responds to the growing demand for convenient RTE food options, particularly among urban consumers with time constraints, while potentially offering a sustainable and innovative approach to traditional snack food production.